RESEARCH ON DEGRADATION CORROSIVE ENVIRONMENT OF SOME STEELS USED IN MANUFACTURING MINING EQUIPMENT. MECHANICAL TESTS - Florin CIOFU; Alin NIOAŢĂ, (Fiabilitate şi Durabilitate)
Simultaneous action of mechanical stress variables and the corrosive environment leads to the deterioration of structures made of steel or of other metallic materials, a process called fatigue in corrosive environment or corrosion fatigue, which has causes and effects different from degradation under the singular action, either of mechanical strain or of corrosive environment. The aim of this paper is the study of the behavior,under fatigue conditions in corrosive environment of low alloy steels meant for the construction of mining equipment used in various mining operations in Gorj county. Based on experimental research regarding sustainability in fatigue corrosion, analyses of the interaction between the mechanical and the electrochemical factors as well as microscopic analyses of the structures we aim in this paper at deeply studying the performance of degradation processes that occur in the surface layers and lead to destruction by corrosion fatigue of the steels under study.